Memaknai Dakwah Digital Melalui Meme Shalat Jum’at Visualisasi Perempuan: Perspektif Semiotika - Sunaryanto Sunaryanto; Sofyan Rizal (Institut Agama Islam Tribakti (IAIT) Kediri, 2023)
The discourse of this research analyzes the da'wah of digital memes with the visualization of women that spread on the internet. In answering these problems, this research uses qualitative research. The mass media textual tool as an analytical tool is used to answer this problem, namely Ferdinand de Saussure's semiotics. This theory is divided into several concepts, namely sign, marker, signified, denotation, and connotation. The results of the study found that the digital da'wah sign in the Friday prayer meme is the headscarf. Digital da'wah markers in memes are women wearing headscarves, the hijab phenomenon, and Muslim women praying. The signs of digital meme propaganda are the reward for Friday prayers, sunnah of the Prophet, and pornography. The denotation meaning of digital da'wah in the meme is that a Muslim man cannot leave the Friday prayer service. Because the characteristics of a good leader or priest for a woman are men who fulfill the obligations of Friday prayer. Connotatively, digital da'wah uses memes to visualize women that Friday prayers only aim to get a woman's reward. The female body, namely the jilboobs, is constructed to call on men to want to perform Friday prayers. Digital da'wah uses memes with connotations because women are constructed as signs, signifiers, and markers to invite men to perform Friday prayers. Muslim women's bodies are constructed as sexual objects to invite Muslim men to perform Friday prayers.